Spectrophotometric determination of sotalol in tablets - Y. M. Zhuk; S. O. Vasyuk (The State Expert Center of the Ministry of Health of Ukraine, 2018)
In this investigation a visible spectrophotometric method for the determination of sotalol based on the absorbance of colored product of the reaction between sotalol hydrochloride and bromcresol purple in acetone medium at 399 nm measurement was developed. The optimal conditions for the quantitative determination of sotalol hydrochloride in the content of pharmaceutical drugs were established. The stoichiometric relationship coefficients between sotalol hydrochloride and bromcresol purple were determined. The validation of the worked out procedure on such validated characteristics as linearity, precision, accuracy and robustness was carried out. The aim. To develop a highly sensitive, easy to use, cost-effective and valid method for quantitative determination of sotalol hydrochloride in dosage forms. The analysis method. Visible spectrophotometry. The analytical parameters such as molar absorptivity, Beer's law limits and Sandell's sensitivity values were calculated. The developed methods give the result with repeatability sufficient for dependable determination the investigated substance in pharmaceutical formulations. Accuracy established by analyte addition technique. Determined factors that influence on the absorbance value: reagent quantity and timing stability. Sample solutions stable during 30 min. Addition to sample solution ± 10% bromcresol purple solution is not change the absorbance value. Established that reaction between sotalol hydrochloride and bromcresol purple proceeds in acetone medium at room temperature. Molar absorption coefficient is 2,62∙10^3.